Biodiversity Conservation and the Earth System: Mind the Gap - Norris, Ken (Trends Ecol Evol, 2020)
One of the most striking human impacts on global biodiversity is the ongoing depletion of large vertebrates from terrestrial and aquatic ecosystems. Recent work suggests this loss of megafauna can affect processes at biome or Earth system scales with potentially serious impacts on ecosystem structure and function, ecosystem services, and biogeochemical cycles. We argue that our contemporary approach to biodiversity conservation focuses on spatial scales that are too small to adequately address these impacts. We advocate a new global approach to address this conservation gap, which must enable megafaunal populations to recover to functionally relevant densities. We conclude that re-establishing biome and Earth system functions needs to become an urgent global priority for conservation science and policy.